Salafism in Indonesia: Ideology, Identity, and Politics - Maharani, Melisa Diah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This article investigates the ideological, identity-based, and geopolitical dynamics of the Salafist movement in Indonesia. Employing qualitative methods through an extensive literature review, the study utilizes Social Identity Theory as its primary analytical framework to examine how Salafi groups construct a distinct collective identity by asserting symbolic and doctrinal boundaries. To complement this framework, the concept of post-Islamism is interpretively applied to capture emerging tendencies within Indonesian Salafism that reveal greater flexibility, pragmatism, and selective engagement with democratic institutions. Findings indicate that while Salafi actors remain committed to doctrinal puritanism, they are simultaneously negotiating their presence in the broader Indonesian Islamic landscape through targeted digital da‘wah strategies and community integration efforts. Internal fragmentation and external socio-political pressures contribute to the development of more contextualized and fluid expressions of Salafism. Rather than a monolithic or static movement, Salafism in Indonesia constitutes a complex, evolving identity shaped by interactions among theology, digital media, state-religion relations, and global ideological currents.